France : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper addresses the question of what policy changes in France are needed under European Monetary Union (EMU), as regards the role of fiscal policy in stabilizing the economy. The fiscal strategy over the past two and a half decades is reviewed, and, against this background, an assessment is offered concerning the role and scope of fiscal stabilizers in France under EMU. The main conclusions is that over the past two and a half decades, fiscal policy operated in a clear countercyclical way in France, but this reflected essentially the functioning of automatic stabilizers.